Ensaio de adensamento com drenagem radial interna e externa - solução teórica - Santa Maria, Paulo Eduardo Lima de (1977)
Presents a theoretical solution to interpret the consolidation tests with internal and external radial drainage. Initially, an exposition on the basic differential equation of consolidation and several existing solutions for radial drainage problems is performed. It is considered, in the formulation of the problem, in addition to the inherent characteristics of the test, the peripheral smear effect which occurs in the preparation of the sample. For this, the sample was subdivided in three distinctive parts which are represented by the internal remolded, undisturbed and the external remolded zone. Along with the general solution, two particular cases are also presented. The general formula is verified by submitting it to extreme conditions which define simple radial drainage models for which theoretical solutions already exist. To simplify the utilization of the developed theory, tables were prepared and curves plotted for various ratios between radii and between permeabilities of disturbed and undisturbed regions. Using the obtained solution, an internal and external radial drainage consolidation test was interpreted, and these results were compared with those encountered for the sarne material, in previous simple radial drainage research.